2021
DOI: 10.24132/csrn.2021.3002.5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2D vs. 3D Unet Organ Segmentation in abdominal 3D CT images

Abstract: A two-step concept for 3D segmentation on 5 abdominal organs inside volumetric CT images is presented. Firsteach relevant organ’s volume of interest is extracted as bounding box. The extracted volume acts as input for asecond stage, wherein two compared U-Nets with different architectural dimensions re-construct an organ segmen-tation as label mask. In this work, we focus on comparing 2D U-Nets vs. 3D U-Net counterparts. Our initial resultsindicate Dice improvements of about 6% at maximum. In this study to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Our study extends the prior literature 10,12,13,32,33 in key ways. We provide the first comprehensive benchmarking of 3D, 2.5D, and 2D auto-segmentation approaches on brain MRIs measuring both accuracy and computational efficiency.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our study extends the prior literature 10,12,13,32,33 in key ways. We provide the first comprehensive benchmarking of 3D, 2.5D, and 2D auto-segmentation approaches on brain MRIs measuring both accuracy and computational efficiency.…”
Section: Discussionsupporting
confidence: 83%
“…Compared to two-dimensional auto-segmentation tasks, the three-dimensional (3D) nature of brain MRIs makes auto-segmentation considerably more challenging (Figure 1). There have been three proposed approaches to handling auto-segmentation of 3D images: 1) analyze and segment one two-dimensional slice of the volume individually one at a time (2D), 10 2) analyze five consecutive two-dimensional slices at a time generate a segmentation the middle slice (2.5D), 11 and 3) analyze and segment the image volume in three-dimensional space (3D). 10 Although each method has shown some promise in medical image segmentation, a comprehensive comparison and benchmarking of these approaches for auto-segmentation of brain MRIs is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…adjacent slices). However, in the case of the U-Net-like architecture, many works [13,14] have reported that both 2D and 3D approaches lead to close results in the context of semantic segmentation for the used medical datasets. To address the issue of missing inter-slice information and bridge the gap further between 2D and 3D strategies, a distance transform was applied to the initial volume before slicing.…”
Section: Network Architecturementioning
confidence: 99%